Drug release as a function of bioactivity, incubation regime, liquid, and initial load: release of bortezomib from calcium phosphate-containing silica/collagen xerogels - Kruppke, Benjamin; Hose, Dirk; Schnettler, Reinhard; Seckinger, Anja; Rößler, Sina; Hanke, Thomas; Heinemann, Sascha (Journal of biomedical materials research. Part B, Applied biomaterials, 2018)
The ability of silica-/collagen-based composite xerogels to act as drug delivery systems was evaluated by taking into account the initial drug concentration, bioactivity of the xerogels, liquid, and incubation regime. The proteasome inhibitor bortezomib was chosen as a model drug, used for the systemic treatment of multiple myeloma. Incubation during 14 days in phosphate-buffered saline (PBS) or simulated body fluid (SBF) showed a weak initial burst and was identified to be of first order with subsequent release being independent from the initial load of 0.1 or 0.2 mg bortezomib per 60 mg monolithic sample. Faster drug release occurred during incubation in SBF compared to PBS, and during static incubation without changing the liquid, compared to dynamic incubation with daily liquid changes. Drug-loaded xerogels with hydroxyapatite as a third component exhibited enhanced bioactivity retarding drug release, explained by formation of a surface calcium phosphate layer. The fastest release of 50% of the total drug load was observed for biphasic xerogels after 7 days during dynamic incubation in SBF. As a result, the presented concept is suitable for the intended combination of the advantageous bone substitution properties of xerogels and local application of drugs exemplified by bortezomib. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 1165-1173, 2018.